Development of Kincir Pintar Pancasila Learning Media to Improve Students’ Understanding in the Pancasila and Civic Education - Naila Rohmaniah; Muhamad Ayyub Mubtadik (Mentari : Journal of Islamic Primary School, 2024)
Learning is a process of interaction between students, educators, and learning resources within a learning environment. At MI Al Huda Kedunglo, particularly in the Pancasila and Civic Education (PPKN) subject, instruction is still predominantly conducted using lecture-based methods, and the limited use of learning media causes students to feel bored. The development of learning media can serve as a solution to help students better understand PPKN materials, especially the topic of the meaning of the national emblem, Garuda Pancasila. The learning media developed in this study is the Kincir Pintar Pancasila. This study aims to examine: (1) the development of Kincir Pintar Pancasila learning media to improve the understanding of Grade III students on the chapter “The Meaning of the National Emblem Garuda Pancasila” in the PPKN subject at MI Al Huda Kedunglo in the 2023/2024 academic year; (2) the validation of the Kincir Pintar Pancasila learning media to improve students’ understanding of the same material; and (3) the effectiveness of the Kincir Pintar Pancasila learning media in improving Grade III students’ understanding of the chapter “The Meaning of the National Emblem Garuda Pancasila.” This research employed the ADDIE development model as proposed by Reiser, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate, using a Research and Development (R&D) research design. Data collection techniques included observations, interviews, questionnaires, and documentation. Data analysis was conducted by converting the scores obtained from material experts, media experts, and students, which were initially qualitative data, into quantitative data. The researcher focused on developing the Kincir Pintar Pancasila learning media by dividing students into several groups and engaging them in learning activities through playing and learning using the media to enhance their understanding. The result of this research and development is a Kincir Pintar Pancasila learning medium containing images of the symbols of Pancasila. Product validation by material and media experts obtained an overall average percentage score of 95%, indicating that the product is valid. Furthermore, the calculation of the N-gain score from the pre-test and post-test results yielded values of 0.71 or 71.6%, indicating that the developed product falls into the “high” score category and demonstrates a “moderately effective” level of effectiveness.